Pengaruh PAD, DAU, DAK, Derajat Desentralisasi dan Ketergantungan Keuangan terhadap Belanja Modal (Studi Empiris pada Kabupaten/Kota Wilayah Jawa Tengah Tahun 2013-2015) - Nurjanah, Desy, Drs. Suyatmin Waskito Adi, M.Si (2017)
In the local expenditure can't be loose from acceptance source, either balance of fund, regional loan, or regional income. Balance of fund is a funding sourced from APBN consisting of divide income fund, general allocation fund, and special allocation fund, while regional income is a funding sourced from regional. The purpose of this study was to obtain empirical evidence about the effect of PAD, DAU, DAK, Degree of Decentralization and Financial Dependence on Capital Expenditure. This research used quantitative research. In this research used taking sample method is saturation sample that is all of population made a research sample. Sample of this research amount to 29 regencies and 6 cities in Central Java Province with 3 years of observation. So the total sample studied was 105. The analysis tool used is the Multiple Linear Regression Analysis. The results of this study indicate that the PAD, DAK and significant effect on the degree of decentralization of Capital Expenditure. While the variable DAK and Financial Dependence no significant effect on Capital Expenditure.